Evaluation of the effects of agricultural LED lighting on in vitro propagation of Cordyceps militaris (Link.) Fries - Hong Gam, Do; Huong Huynh, Duong; Thi Lan Anh, Phan; Hoang Duong, Nguyen; Thi Kim Hoa, Do (Vietnam Journal of Biotechnology, 2020)
In this study, the effects of various agricultural LED lights (LED NN), including single red LED (R), single blue LED (B), and four combinations of blue, red, and warm white (W) LED (BR, BRW1, BRW2, BRW3) on the growth and development of C. militaris (Link.) Fries were evaluated in vitro. After 7 days, samples subjected to LED NN showed shorter sporocarp sprouting time and higher sprouting ratio than the control, which was subjected to T5 fluorescent light. After 2 months, LED lights with high red ratio, such as single red LED and LED BR, had suppressing effect on the growth and development of C. militaris (Link.) Fries. On the other hand, combinations of red, blue, and warm white such as LED BRW1, LED BRW2, and LED BRW3 had the positive impact on the growth and development of this fungus. Notably, samples subjected to LED BRW2 reached 5.79 cm in height, fresh biomass of 3.67 g/20 samples. Cordycepin and Adenosine levels were 64.2 and 6.37 mg/100 g fresh mass, respectively. All of studied indicators were the higher compared to those of the control and other LED lighting schemes. Therefore, it can be conlcuded that LED lighting combination with BRW2 ratio of 1:5:1 and luminous intensity of 45±2 µmol.m-2.s-1 (511,59 Lux) was suitable for the growth and development of C. militaris (Link.) Friesand a potential replacement of fluorescent light for C. militaris (Link.) Friesin vitro propagation.